Dietary Diversity, Stunting, and the Impact of an Education Program on Parents’ Knowledge and Attitudes in West Sumba, Indonesia - Hendryanti, Dea Nathania; Andriani, Cynthia; Indriani, Sylvia; Gunawan, Lidyawati; Sibero, Mada Triandala (Jurnal Gizi dan Pangan, 2023)
This pre- and post-test quasi-experimental study aimed to assess dietary diversity and its association with stunting among toddlers (13–60 months), examine the levels of knowledge and attitudes towards balanced and diverse diets among parents or caregivers, and evaluate the impact of customized flashcards and meal boxes as educational tools on parents’/caregivers’ knowledge and attitudes in three selected villages in West Sumba, Indonesia. A total of 59 parents/caregivers were recruited, 30% of whom had stunted toddlers. The levels of parents’/caregivers’ knowledge and attitudes were moderate. The results from the pre-test study show that Dietary Diversity Score (DDS) did not correlate with stunting status. Furthermore, neither knowledge nor attitudes was discovered to be related to DDS. The use of flashcards and meal boxes in the educational program improved the scores of knowledge (p<0.05) and attitudes (p<0.05) from the pre-test scores. There was a positive correlation between knowledge and attitudes, either before or after the education program (r=0.362, p<0.05 and r=0.562, p<0.05, respectively). To summarize, this study has the potential to be applied in other rural and remote areas.